VARIASI GEJALA COVID-19 YANG DIALAMI PERAWAT MURNI TEGUH MEMORIAL HOSPITAL - Seriga Banjarnahor (STIKes Murni Teguh, 2020)
COVID-19 is a virus that threatens health throughout the world. The spread of this virus is very fast and people who are exposed to COVID-19 generally bring out symptoms that have not yet to be fully explained. This study aims to know the symptoms of COVID-19 experienced by nurses at Murni Teguh Memorial Hospital who were confirmed positive COVID-19. This type of research is a quantitative research with a descriptive design. The number of respondents in the study was 31 nurses, which were obtained by using the total sampling method. The results of this study indicate that the symptoms experienced by nurses are vary, ranging from asymptomatic (22,4%) and the dominant symptoms felt by nurses such as loss of smell (64,5%), fever (54,8%), and cough (51,6%). Abstrak COVID-19 merupakan virus yang mengancam kesehatan sampai saat ini di seluruh dunia. Penyebaran virus ini sangat cepat dan orang yang terpapar COVID-19 umumnya menimbulkan suatu gejala yang hingga saat ini belum sepenuhnya dapat dijelaskan. Penelitian ini bertujuan untuk mengetahui gejala COVID-19 yang di alami perawat Murni Teguh Memorial Hospital yang terkonfirmasi positif COVID-19. Jenis penelitian yang digunakan adalah penelitian kuantatif dengan desain deskriptif. Responden penelitian berjumlah 31 perawat, yang diperoleh dengan metode total sampling. Hasil penelitian ini menunjukkan gejala yang di alami perawat bervariasi, mulai dari asimptomatik (22,4%), dan gejala dominan yang dirasakan perawat seperti hilangnya indera penciuman (64,5%), demam (54,8%), dan batuk (51,6%).